Urgensi Demokrasi dalam Upaya Pembentukan Negara Ideal Menurut Muhammad Syahrur - Muwahhidin, M. Agus (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2013)
Democracy for Shahrur is a representation of the concept of shura in modern time. This is because the concept of shura is a part of the dialectic of life. Therefore, It is subject to change, depending on space and time. This is what Shahrur called as the term of value and technical point of shura. As for the pressure point of democracy is subject to shariâ€™ah. Such understanding is evidenced by a definition that democracy is the practice of freedom by a group of humans in accordance with the authority of knowledge, ethics, aesthetics, customs, and religious laws. The urgency of democracy in the efforts to establish the ideal state, which according to Shahrur isÂ called a â€œsecularâ€ countr is a state that bases its legitimacy from the people and not from the religious scholars. It is also a country that does not recognize the existence of the guards of the Godâ€™s laws. In addition to developing science, democracy can also minimize the potential of friction because it is not talking about primordialism but more about the common interest.